PENGARUH INTENSITAS MENONTON CHANNEL YOUTUBE BLACKPINK TERHADAP PERILAKU IMITASI REMAJA: Survei Pada Pengikut Akun Instagram @Blackpinkpage_id - Nilamsari Putri Amanatillah (2022)
Behavior is not formed instinctively from birth but is influenced by environmental factors. Social media makes culture easy to spread so that the consumption of foreign cultures, especially K-Pop in Indonesia, is very high. The intensity of watching the Blackpink girl group Youtube channel in Indonesia is very high, especially among teenagers. This study aims to see the effect of the intensity of watching the Blackpink Youtube channel on the imitation behavior of teenagers on followers of the @blackpinkpage_id Instagram fanbase account. The research uses social learning theory by Albert Bandura. Bandura's theory of social learning has the assumption that individual behavior is formed through the environment by imitation. This study uses the positivism paradigm by using quantitative methods with explanative types. The population in this study are followers of the Instagram fanbase account @blackpinkpage_id with a sample of 100 respondents. The results showed that there was a moderate relationship between the intensity of watching the Blackpink Youtube channel and adolescent imitation behavior with a correlation coefficient of 0.559. The intensity of watching the Blackpink Youtube channel has a significant positive effect on adolescent imitation behavior with a coefficient of determination of 32.6% and the remaining 67.4% is influenced by other factors not examined. The novelty finding of this research is that the aspects of the Korean wave that are most imitated by teenagers are songs and dances as well as foreign languages, while the style of dress is the aspect that has the lowest imitation.